PELATIHAN PERAWATAN AIR CONDITIONER (AC) UNTUK SISWA SMK PENERBANGAN DIRGHANTARA - Yenni Arnas; Hari Kurniawanto; Zulina Kurniawati; Benny Kurnianto; Imam Haryadi; KGS. M. Ismail; Nawang Kalbuana; M. Samudera Novarizki Adityanto Nursin (Jubaedah : Jurnal Pengabdian dan Edukasi Sekolah (Indonesian Journal of Community Services and School Education), 2024)
Most students at the aviation vocational high school focus on learning about aircraft maintenance techniques i.e. Airframe and Powerplant and also Electrical Avionic. On the other hand, the aviation industry involves various fields of expertise such as navigation, aircraft maintenance, electricity, mechanics, civil engineering, etc. Furthermore, airport mechanical engineering becomes one of the most demanded competence in the aviation industry to fill vacancy as technicians in 340 airports in Indonesia. Therefore, the community service team carried out a training program for students at Dirghantara Aviation Vocational High School in maintaining air conditioner (AC) as one of the required competencies for airport mechanical technicians. The method used in this activity is which includes classroom learning and field practice. The result of this activity showed that the students obtained one of the airport mechanical competency i.e. AC maintenance skill. According to the evaluation, the training participants stated that the activity was valuable. They awaited that other mechanical competency education and training would be given